2002
DOI: 10.1002/neu.10161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quantitative trait loci that influence animal behavior

Abstract: Behavioral differences between inbred strains of mice and rats have a genetic basis that can now be dissected using quantitative trait locus (QTL) analysis. Over the last 10 years, a large number of genetic loci that influence behavior have been mapped. In this article I review what that information has revealed about the genetic architecture of behavior. I show that most behaviors are influenced by QTL of small effect, each contributing to less than 10% of the variance of a behavioral trait. The small effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
143
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 125 publications
(93 reference statements)
12
143
0
2
Order By: Relevance
“…The largest QTL, Tame-1, explains 5.1% of the residual phenotypic variance, while the remaining loci each explain smaller fractions when considered individually. These estimates are in line with the generally small effect sizes reported for QTL for other rodent behaviors (Flint 2003). Across 45 measures and three principal component scores, our study identified 23 significant and 125 suggestive QTL.…”
Section: Discussionsupporting
confidence: 88%
“…The largest QTL, Tame-1, explains 5.1% of the residual phenotypic variance, while the remaining loci each explain smaller fractions when considered individually. These estimates are in line with the generally small effect sizes reported for QTL for other rodent behaviors (Flint 2003). Across 45 measures and three principal component scores, our study identified 23 significant and 125 suggestive QTL.…”
Section: Discussionsupporting
confidence: 88%
“…The small effect size of each genetic locus in psychiatric disorders suggests that the causal genetic variations may regulate gene expression levels rather than result in protein coding sequence variation. 25 Hence, examination of cis eSNP associations within the candidate genes is a reliable approach for identification of strong candidate genes for complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this may be due to two factors. First is the lower power of these earlier studies, with smaller Ns and genotyping of only extreme behavioral phenotypes, which greatly increases the chances of false negatives (Flint, 2003). Second is the opposing effects of the Ch7 QTL-increased activity in safe areas but substantial suppression of activity in bright areas and open runways-which may counteract each other in some test situations.…”
Section: Qtl Analysis Of Anxiety In Mice 281mentioning
confidence: 99%